Image compression and encryption - Zainal Abidin, Zuhairiah (2003)
Uncompressed multimedia data (image) requires considerable storage capacity. However, all classified image file, has to be protected against unauthorized access. The purpose of this project was to implement the combinational of image compression and encryption to overcome this problem. In this project, the image compression process involved the usage of the wavelet transform. Eight images have been used in this project for its implementation. The original image was decomposed until ten levels of decomposition by using Daubechies2 (db2). The aforementioned was recursively done from Daubechies2 (db2) to DaubechieslO (db 10). After the decomposition stage, the image that performs optimum percentage of coefficients was suppressed to zero (PERFO) and the percentage of perfect reconstruction (PERFL2) is chosen. Thereafter, the chosen image was compressed and finally, encrypted. In this project, the RC4 encryption algorithm has been used. This project utilized MATLAB Wavelet Toolbox Version 6.5 thoroughly for its implementation. The output of the image compression and encryption was then be analyzed by using mean-square error (MSE), peak signal to noise ratio (PSNR), percentage of coefficients suppressed to zero (PERFO) and percentage of perfect reconstruction (PERFL2).